2016
DOI: 10.4238/gmr.15037819
|View full text |Cite
|
Sign up to set email alerts
|

Role of IL-10 and TNF-α during Mycobacterium tuberculosis infection in murine alveolar macrophages

Abstract: ABSTRACT. Mycobacterium tuberculosis (Mtb) is known to be responsible for tuberculosis (TB), but the pathogenesis of this disease and the host defense mechanisms involved are, for the most part, poorly understood. In this study, we divided 30 male C57BL/6 mice into control and infection groups, and following injection with physiological saline or Mtb, respectively, euthanized five mice from each group on days 1, 3, and 7. TNF-a and IL-10 levels were measured by enzyme-linked immunosorbent assay and flow cytome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…In addition, IL-10 can stimulate T and B lymphocytes, and IL-10 can also stimulate T and B lymphocytes in patients with tumor. Some studies have shown that an increase in cellular IL-10 secretion is related to the susceptibility to PTB ( 29 ). The serum level of IL-10 in patients with PTB is higher than that in healthy controls, which inhibits the production of pro-inflammatory factors by monocytes and macrophages, weakens the antigen presentation of macrophages, and reduces the clearance of M. tuberculosis by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, IL-10 can stimulate T and B lymphocytes, and IL-10 can also stimulate T and B lymphocytes in patients with tumor. Some studies have shown that an increase in cellular IL-10 secretion is related to the susceptibility to PTB ( 29 ). The serum level of IL-10 in patients with PTB is higher than that in healthy controls, which inhibits the production of pro-inflammatory factors by monocytes and macrophages, weakens the antigen presentation of macrophages, and reduces the clearance of M. tuberculosis by the immune system.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is an inhibitory and anti-inflammatory cytokine that inhibits the ability of myeloid cells such as macrophages and dendritic cells to activate cytokine production from Th1 cells such as TNF-α & IFN-γ. Thus IL-10 is an immunosuppressive cytokine that can inhibit macrophage functions, resulting in enhanced intracellular bacterial growth (18,19). Thus, the balance between TNF-α & IFN-γ and IL-10 produced by macrophages against TB is thought to modulate immune response against TB infection (20,21).…”
Section: Discussionmentioning
confidence: 99%